Mzabimycins A and B, novel intracellular angucycline antibiotics produced by Streptomyces sp. PAL114 in synthetic medium containing L-tryptophan - Samira Tata; Adel Aouiche; Christian Bijani; Noureddine Bouras; Frédéric Pont; Florence Mathieu; Nasserdine Sabaou (Elsevier, 2019)
In our previous studies, the production of four bioactive molecules by Streptomyces sp. PAL114 in complex ISP2 broth medium has been described. Three of these molecules belong to the angucycline family. In this study, two novel antibiotics belonging to the same family were produced by strain PAL114 on M2 synthetic medium containing L-tryptophan as precursor. These antibiotics, named mzabimycins A and B, were intracellular and produced only in the presence of L-tryptophan. After four days of culturing PAL114 in the M2 medium, the bioactive compounds were extracted from mycelium with methanol and then analyzed by HPLC on reverse phase C18 column. Two active purplish blue fractions were purified. The chemical structures of these molecules were determined on the basis of spectroscopic and spectrometric analyses (1H and 13C NMR, and mass spectra). They were identified to be novel angucycline derivative antibiotics. The pure molecules showed activity against some pathogenic Gram-positive bacteria which have multiple antibiotic resistance, such as Staphylococcus aureus MRSA 639c and Listeria monocytogenes ATCC 13932. Keywords: Antimicrobial compounds, Angucycline antibiotics, L-Tryptophan, Synthetic medium, Streptomyces